# tg 2α

=

tg 2α =

1
1
− 1 ctg 2α =
−1
2
cos α
sin 2 α
2tgα
1 − tg 2α

ctg α − 1
2ctgα
2tgα
1 − tg 2α
sin 2α =
cos
2
α
=
1tg 2α
1tg 2α
α
α
α
α
sin α = 2 sin ⋅ cos
cos α = cos 2 − sin 2
2
2
2
2
α
α
2tg
ctg 2 − 1
2
2
tgα =
ctgα =
α
2 α
1 − tg
2ctg
2
2
tg 2α =

2

ctg 2α =

sin ( α ± β ) = sin α ⋅ cos β ± sin β ⋅ cos α

sin α ± sin β = 2 sin

α+β
α −β
⋅ cos
2
2

30

sin

½

cos
tg
ctg

45

α+β
α −β
⋅ sin
2
2

3 /2
3 /3
3

1
1

60

2/2
3 /2
2/2 ½
3
3 /3

α ±β
α β
⋅ cos
2
2

cos α + cos β = 2 cos

α+β
α −β
⋅ cos
2
2

cos α − cos β = −2 sin

Cosinusna teorema
a 2 = b 2 + c 2 − 2bc ⋅ cos α
b 2 = a 2 + c 2 − 2ac ⋅ cos β
c 2 = a 2 + b 2 − 2ab ⋅ cos γ

α

ctg 2α =

cos( α ± β ) = cos α ⋅ cos β sin α ⋅ sin β

α ±β
α β
sin α ± sin β = 2 sin
⋅ cos
2
2

cos α − cos β = −2 sin

2tgα
1 − tg 2α

ctg 2α − 1
2ctgα
2tgα
1 − tg 2α
sin 2α =
cos 2α =
1tg 2α
1tg 2α
α
α
sin α = 2 sin ⋅ cos
2
2
α
α
cos α = cos 2 − sin 2
2
2
α
α
2tg
ctg 2 − 1
2
2
tgα =
ctgα =
α
α
1 − tg 2
2ctg
2
2
tg 2α =

sin ( α ± β ) = sin α ⋅ cos β ± sin β ⋅ cos α

cos( α ± β ) = cos α ⋅ cos β sin α ⋅ sin β

cos α + cos β = 2 cos

1
1
− 1 ctg 2α =
−1
2
cos α
sin 2 α

α+β
α −β
⋅ sin
2
2

Cosinusna teorema
a 2 = b 2 + c 2 − 2bc ⋅ cos α
b 2 = a 2 + c 2 − 2ac ⋅ cos β
c 2 = a 2 + b 2 − 2ab ⋅ cos γ

π

2
π

3
π/2

0

π
/
2
1

0

-1

-1

0

1

0

0

0

-∞

-∞

0

0

α

30

sin

½

cos
tg
ctg

45

3 /2
3 /3
3

1
1

60

2/2
3 /2
2/2 ½
3
3 /3

π

2
π

3
π/2

0

π
/
2
1

0

-1

-1

0

1

0

0

0

-∞

-∞

0

0